Increasing the field of view of x-ray phase contrast imaging using stitched gratings on low absorbent carriers - Meiser, J.; Amberger, M.; Willner, M.; Kunka, Danays; Meyer, Pascal Edouard; Koch, Frieder; Hipp, A.; Walter, M.; Pfeiffer, F.; Mohr, J. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2014)
X-ray phase contrast imaging has become a promising biomedical imaging technique for enhancing soft-tissue contrast. In addition to an absorption contrast image it provides two more types of image, a phase contrast and a small-Angle scattering contrast image recorded at the same time. In biomedical imaging their combination allows for the conventional investigation of e.g. bone fractures on the one hand and for soft-tissue investigation like cancer detection on the other hand. Among the different methods of X-ray phase contrast imaging the grating based approach, the Talbot-Lau interferometry, has the highest potential for commercial use in biomedical imaging at the moment, because commercially available X-ray sources can be used in a compact setup. In Talbot-Lau interferometers, core elements are phase and absorption gratings with challenging specifications because of their high aspect ratios (structure height over width). For the long grating lamellas structural heights of more than 100 Î=m together with structural width in the micron range are requested. We are developing a fabrication process based on deep x-ray lithography and electroforming (LIGA) to fabricate these challenging structures. In case of LIGA gratings the structural area is currently limited to several centimeters by several centimeters which limit the field of view in grating based X-ray phase contrast imaging. In order to increase the grating area significantly we are developing a stitching method for gratings using a 625 Î=m thick silicon wafer as a carrier substrate. In this work we compare the silicon carrier with an alternative one, polyimide, for patient dose reduction and for the use at lower energies in terms of transmission and image reconstruction problems. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biomedical imaging; carrier substrate; field of view; LIGA; stitched grating; Talbot-Lau interferometry; X-ray phase contrast imaging